The Effect of the Time Token Cooperative Learning Model on Fifth-Grade Elementary Students' Learning Outcomes - Rachel Monica Sidauruk; Patri Janson Silaban; Bogor Lumbaraja; Regina Fredrika Sipayung; Rumiris Lumban Gaol (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This study examines the effect of the Time Token learning model on students’ learning outcomes in Grade V at SD Negeri 060938 Medan Johor during the 2022/2023 academic year. The research employed a quantitative approach with a correlational design. The population of the study consisted of 30 fifth-grade students, all of whom were selected as research subjects through probability sampling, resulting in a total sample of 30 students. Data were collected to measure students’ learning outcomes after the implementation of the Time Token learning model. The results indicate that students’ learning outcomes achieved through the application of the Time Token model fall into the very good category, with an average score of 80.3. Statistical analysis revealed a correlation coefficient of 0.701, which exceeds the critical value of rtable = 0.361, indicating that Ha is accepted. This result demonstrates a significant relationship between the use of the Time Token learning model and students’ learning outcomes. Furthermore, hypothesis testing using the t-test showed that tcount = 5.196 is greater than ttable = 1.701, further confirming the acceptance of Ha. Based on these findings, it can be concluded that the Time Token learning model has a significant and positive effect on students’ learning outcomes in Grade V at SD Negeri 060938 Medan Johor during the 2022/2023 academic year. The implementation of this model effectively enhances student participation and learning achievement, making it a viable instructional strategy for elementary school classrooms.